Sociodemographic and mental health characteristics of children who use mental health care for specific reasons. (June 2023) - Eijgermans, D.G.M.; Jansen, P.W.; Shuker, A.M.; Heydelberg, J.F.P.; Raat, H.; Jansen, W.
Highlights: Mental health care use was most often obtained for behavioural problems. Emotional problems, behavioural problems, other psychosocial problems and life events and family problems as reasons for care use were associated with multiple sociodemographic characteristics and earlier reports on mental health problems. Social problems, physical problems, cognitive developmental problems and other problems as reason for care use were not found to be associated with sociodemographic or earlier mental health characteristics. Abstract: Purpose: In this study, we aimed to identify for what reasons children receive mental health care and what sociodemographic and mental health characteristics are associated with these specific reasons. Methods: This study investigated 777 children who consulted a psychologist/psychiatrist between 9 and 13 years old. Data were retrieved from the Generation R Study, a population-based cohort in Rotterdam, the Netherlands. Sociodemographic and mental health characteristics were measured between birth and 13 years old. Logistic regression analyses were used to study the characteristics that were associated with eight parent-reported reasons for mental health care use. Results: Behavioural problems were most often mentioned as reason for mental health care use (36 %), followed by life events and family problems (15 %) and emotional problems (15 %). Several sociodemographic and mental health characteristics were associated with some of the reasons for care use. Sex was most frequently associated with the reasons for care use. Life events and family problems as reason for care use were associated with most sociodemographic characteristics, e.g. migrant origin and family situation. No associations were found for the children using mental health care for social problems, physical problems, cognitive developmental problems and other problems. Conclusion: Distinctive profiles of sociodemographic characteristics were found for some reasons for care use, while for other reasons no associations were found with sociodemographic or mental health characteristics. Implications of these findings and suggestions for future research are discussed. In conclusion, this study provides some insights into the profiles of care users, but still many questions remain.